The monoclonal antibody, UCHL1, recognizes a 180,000 MW component of the human leucocyte-common antigen, CD45. - Terry, L; Brown, M; Beverley, P (1988)
The leucocyte-common antigen (L-CA or CD45) is a family of high molecular weight glycoproteins, ranging from 180,000 to 220,000 MW that are expressed only on cells of lymphoid and myeloid origin. CD45 monoclonal antibodies (mAbs) recognize epitopes present on all polypeptides of the family, while other mAbs, termed CD45R, recognize determinants found only on the 220,000 MW and 200,000 MW polypeptides. In contrast the mAb UCHL1 recognizes a 180,000 MW antigen. UCHL1-coupled Sepharose beads were used to absorb antigen from lysates of cell lines. CD45 mAbs bound to this immobilized antigen. Antigen immobilized with CD45 mAb-coupled Sepharose beads bound UCHL1. Antigen purified by absorption and elution from the MOLT-4 cell line with CD45 mAb-coupled beads yielded molecules of 180,000 and 190,000 MW. Reprecipitation of the eluted antigen with UCHL1 resulted in a 180,000 MW band only. In a reciprocal experiment, CD45 mAb reprecipitated a 180,000 MW molecule from purified UCHL1 antigen. UCHL1 and the CD45R mAb 2H4 showed a mutually exclusive pattern of reactivity with human T- and B-cell lines, but co-expression of the antigens was seen on two myeloid and one erythroleukaemic cell line. In contrast, epitopes recognized by other putative CD45R mAbs were co-expressed with UCHL1 both on myeloid, erythroid and many T- and B-cell lines. We conclude that UCHL1 recognizes an epitope present only on the 180,000 MW polypeptide of CD45. Expression of this antigen is essentially reciprocal to the epitope detected by the CD45R mAb 2H4.